Determining the Effectiveness of Visual Input Enhancement Across Multiple Linguistic Cues. Issue 1 (31st August 2017) - Comeaux, Ian; McDonald, Janet L.
Abstract: Visual input enhancement (VIE) increases the salience of grammatical forms, potentially facilitating acquisition through attention mechanisms. Native English speakers were exposed to an artificial language containing four linguistic cues (verb agreement, case marking, animacy, word order), with morphological cues either unmarked, marked in the same color, or marked in different colors. Cue validity (how often a cue was present and correct) and dominance were also manipulated. In Experiment 1, where the morphological cues were low in validity but highly dominant, VIE helped participants to acquire and strengthen one morphological cue (case marking) but not the other (verb agreement). In Experiment 2, where animacy was highly dominant, there was no benefit of VIE; indeed, the same color VIE condition impeded the acquisition of the marked cues. Thus, VIE may only be beneficial in certain circumstances and this may depend on the type of cue as well as its validity and dominance. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . All data are publicly accessible via the Open Science Framework athttps://osf.io/re48w . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .